DETERMINAN PENGELOLAAN DANA DESA DI KECAMATAN RUPIT PROVINSI SUMATERA SELATAN - AL-Fiansyah, Rafi; Oktarida, Anggeraini; Husni Mubarok, Muhammad (Jurnal Akuntansi AKTIVA, 2025)
The aim of this research is to determine the influence of Apparatus Competence, Accountability and the Government's Internal Control System on Village Fund Management in Rupit District. The population in this study were 16 villages in Rupit District. This research used a saturated sampling technique with 64 respondents. Data was collected by distributing questionnaires directly to respondents. The data analysis technique used is multiple linear regression with the help of SPSS 29 software. The results of this research show that Apparatus Competence, Accountability and the Government's Internal Control System partially and simultaneously have a positive and significant effect on Village Fund Management. The Adjusted R Square value is 0.621, which means that Apparatus Competence, Accountability and the Government's Internal Control System have an influence of 62.1% on Village Fund Management.